OPTIMALISASI PERAN KADER POSYANDU DALAM PENINGKATAN STATUS TUMBUH KEMBANG BALITA - Ridlo Septian Reslanto; Tri Sakti Widyaningsih; Sri Mulyanti (Optimal Nursing Journal, 2026)
Introduction: Growth and development is an important aspect in a child's life which is basically two different events but both are interrelated. At this time, growth and development disorders in children that are often found include physical disorders, motor development, language and behavior. Physical growth disorders in children can include wasting, stunting, overweight, while child development disorders can include behavioral deviations, delays in gross motor skills, fine motor skills, speech and language, as well as socialization and independence. In handling cases of growth and development disorders, the government takes initial preventive measures, namely screening which can be carried out at posyandu. Posyandu with several programs to handle children's growth and development which are implemented by posyandu cadres. Methods: This research was conducted using a correlational method with a cross-sectional approach. The sampling technique used was proportionate random sampling for posyandu cadres and accidental sampling for toddlers with a population of 40 respondents from posyandu cadres and toddlers. Results: The results of the Chi-Square Test using the Fisher Exact Test alternative obtained a p-value of 0.000. Thus, the role of toddler posyandu cadres is related to the level of growth and development of toddlers. Discussion/Suggestion: There is a relationship between the role of toddler posyandu cadres and the level of growth and development of toddlers.